2021
DOI: 10.21037/atm-20-7765
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of blood cell parameters and inflammatory factors in 92 patients with COVID-19

Abstract: Background: Although there are many COVID-19 case series studies, few studies report the relationship between variations in blood cell parameters and inflammatory factors and disease severity. This study aims to describe the dynamic trends in COVID-19 blood cell parameters and inflammatory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It was found that the CRP concentration is almost positively correlated with the degree of inflammation and tissue injury 37 . Many studies have reported that CRP is helpful in the diagnosis of inflammatory diseases, such as neonatal sepsis 38 , COVID-19 39 , pneumonia 40 , and influenza 41 . However, CRP alone cannot distinguish sepsis from SIRS due to its elevated level in both conditions 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the CRP concentration is almost positively correlated with the degree of inflammation and tissue injury 37 . Many studies have reported that CRP is helpful in the diagnosis of inflammatory diseases, such as neonatal sepsis 38 , COVID-19 39 , pneumonia 40 , and influenza 41 . However, CRP alone cannot distinguish sepsis from SIRS due to its elevated level in both conditions 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be used as an important marker for the diagnosis of infectious diseases. The current CRP assay is diverse, rapid, and inexpensive, so the CRP concentration is used in a regular manner for the diagnosis, differential diagnosis and prognosis of SARS-CoV-2 infection in the management of COVID-19 [12]. In this study, the CRP concentration in the bacteria-positive group was signi cantly higher than that in the bacteria-negative group, suggesting that CRP was signi cantly increased in in ammation caused by bacterial coinfection, but the increase was not signi cant in SARS-CoV-2-positive patients without bacterial coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis at only a single time point may conceal alterations in the parameters of an individual patient when the patient's condition changes, and it may not demonstrate diversification with disease aggravation. Recent studies analyzed a series of large sample cohorts, which included complete data on patients with COVID-19 in different disease states ( 1 , 20 , 22 ); however, there is limited research on dynamic changes in blood cell parameters and inflammatory factors to characterize disease progression and their profiling in the long-term perspective. The immune cells from the peripheral blood of a patient may be used as markers for COVID-19 and can be analyzed using fast and easily accessible blood tests ( 21 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%